2005
DOI: 10.1179/174329005x73838
|View full text |Cite
|
Sign up to set email alerts
|

Green strength of powder compacts provided for production of highly porous titanium parts

Abstract: The production route of highly porous near net shape titanium parts includes the green machining of compacts made of metallic and pore former (often ammonium bicarbonate) powder mixtures. Success in green machining greatly depends on compact strength. The aim of the present work was to determine and quantitatively evaluate factors influencing the green strength of titanium-ammonium bicarbonate compacts. The substantial dependence of green strength on the amount of pore former and compaction pressure was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
16

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 9 publications
1
31
0
16
Order By: Relevance
“…Conversely, Batch 2 powder, despite the fact that it has the highest slide coefficient and higher apparent density, reaches the lowest densities due to its high equivalent oxygen. Data from other authors [17,18] has been used to validate this hypothesis. Table 6 shows the correlation between the equivalent oxygen and the compressibility.…”
Section: Interpretation Of Titanium Powders Compressibility Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Batch 2 powder, despite the fact that it has the highest slide coefficient and higher apparent density, reaches the lowest densities due to its high equivalent oxygen. Data from other authors [17,18] has been used to validate this hypothesis. Table 6 shows the correlation between the equivalent oxygen and the compressibility.…”
Section: Interpretation Of Titanium Powders Compressibility Resultsmentioning
confidence: 99%
“…Few papers have studied the compaction of Ti powders [14][15][16][17][18]. This work is focused on the different aspects related to the uniaxial pressing of Ti powder in comparison with the well-known behaviour of commercial iron powder.…”
Section: Introductionmentioning
confidence: 99%
“…A powder layer is deposited and melted selectively in an alternate fashion, until the entire, permanently integrated real object is created. The excess powder, removed from a working platform, can be re-used, by collecting it into a separate special magazine, after being inely sifted in subsequent fabrication processes [37,38]. An example of a scafold observed with a bare eye, whose size matches the palate loss of one of the patients participating in clinical trials, is shown in Figure 7, showing, respectively, view from the top (Figure 7a) and from the botom (Figure 7b).…”
Section: Selective Laser Melting Of Scafoldsmentioning
confidence: 99%
“…Pese a que no existe unanimidad en relación al tamaño de poro idóneo que permita la adhesión y crecimiento de los osteoblastos, diversos autores lo sitúan entre 100 y 500 μm [Simske 1997, Wen 2002b, Kupp 2002, Dewidar 2005, Takemoto 2006, Bansiddhi 2008, tal que permita desarrollar los conductos sanguíneos por una parte ( § 450 m), y las células del hueso por otra ( § 100 m) [Bram 2005]. …”
Section: Porosidad Y Tamaño De Poro a Desarrollarunclassified
“…Por ello, mientras que métodos como la síntesis reactiva apenas han sido investigados, la viabilidad de otros procesos, como la técnica de HIP con gas atrapado [Degischer 2002], la sinterización de microesferas [Cirincione 2002, Thieme 2001, o el método de espaciadores [Bram 2005, Laptev 2004] si ha sido demostrada. Kupp 2002, Ryan 2006, Esen 2007.…”
Section: Métodos De Modificación De La Rigidez Empleados En Titaniounclassified